2015
DOI: 10.1098/rsif.2015.0644
|View full text |Cite
|
Sign up to set email alerts
|

Interactional leader–follower sensorimotor communication strategies during repetitive joint actions

Abstract: Non-verbal communication is the basis of animal interactions. In dyadic leaderfollower interactions, leaders master the ability to carve their motor behaviour in order to 'signal' their future actions and internal plans while these signals influence the behaviour of follower partners, who automatically tend to imitate the leader even in complementary interactions. Despite their usefulness, signalling and imitation have a biomechanical cost, and it is unclear how this cost-benefits trade-off is managed during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
88
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 78 publications
13
88
1
Order By: Relevance
“…This result highlights the presence of visuo-motor interference between self-executed actions and those observed in the partner as an index of automatic imitation. These results mirror previous studies 2013;2015b;Candidi et al, 2015;Curioni et al, 2017), only in the condition during which predictions about the partner's movements are needed. Visuo-motor interference effects were present only when performing power grips on the lower part of the bottle as, when performing precision grips on the upper part of the bottle, the maximum wrist height is always reached when touching the bottle -thus impossible to modulate.…”
Section: Maximum Wrist Height (Maxh)supporting
confidence: 89%
See 1 more Smart Citation
“…This result highlights the presence of visuo-motor interference between self-executed actions and those observed in the partner as an index of automatic imitation. These results mirror previous studies 2013;2015b;Candidi et al, 2015;Curioni et al, 2017), only in the condition during which predictions about the partner's movements are needed. Visuo-motor interference effects were present only when performing power grips on the lower part of the bottle as, when performing precision grips on the upper part of the bottle, the maximum wrist height is always reached when touching the bottle -thus impossible to modulate.…”
Section: Maximum Wrist Height (Maxh)supporting
confidence: 89%
“…We used an ecological and controlled human-avatar interactive task (Sacheli et al, 2015a;2015b;Candidi et al, 2017;Era et al, 2018a;Gandolfo et al, 2019), which has been shown to recruit the same behavioural processes called into play during human-human interaction, namely mutual adjustment and automatic imitation 2013;Candidi et al, 2015;Curioni et al, 2017;Era et al, 2018b). Importantly, in the present task, one's own action goal cannot be achieved without considering the virtual partner's online movements and adapting to them.…”
Section: Experimental Taskmentioning
confidence: 99%
“…Whereas in other areas of social interaction research neuroscientific methods are used online during naturalistic behavioural paradigms (Kourtis et al, 2010;Meyer et al, 2011;Candidi et al, 2015;Sacheli et al, 2015a), this has rarely been realized in mimicry research (for exceptions see Hogeveen et al, 2015b;van Ulzen et al, 2013). Instead, our understanding of the neural mechanisms of behavioural mimicry is limited to indirect translations from neuroimaging during observation of simple behaviours and RCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on sensorimotor communication employed interpersonal coordination tasks where task information was distributed asymmetrically such that one actor had information that the other was lacking. To provide the missing information to their co-actors, informed actors then modulated certain kinematic parameters of their actions, such as movement direction (Pezzulo & Dindo, 2011;Pezzulo et al, 2013), movement amplitude (Sacheli et al, 2013;Vesper & Richardson, 2014), or grip aperture (Candidi et al, 2015;Sacheli et al, 2013), thereby informing their co-actors about an intended goal location.…”
Section: Previous Research On Sensorimotor Communicationmentioning
confidence: 99%
“…To date, experimental studies (Candidi, Curioni, Donnarumma, Sacheli, & Pezzulo, ; Sacheli, Tidoni, Pavone, Aglioti, & Candidi, ; Vesper & Richardson, ) as well as theoretical work (Pezzulo et al., ) on sensorimotor communication have almost exclusively focused on joint actions where interaction partners needed to communicate about spatial locations of movement targets (but see Vesper, Schmitz, Safra, Sebanz, & Knoblich, , for an exception). This raises the question of whether sensorimotor communication can more generally help with achieving joint action coordination.…”
Section: Introductionmentioning
confidence: 99%